(3CQLhRI aj GdfZeGJ hGdVQhH GdehSjbjIs - (3eMeO Hf eMeO Hf CMeO GdPgHj, GHf GdUHGMs
(3ChdgG (B:s
(3aEfi deG eGQSJ Yde GdehSjbi hCJbfJg YdekG hYedG QSJ YQGb ChGRge fjQhRaQhYgG HjfgeG eQchR s
(3Ke aUd dCMeO GdLZGfGFi Ke QSGdI HYfhGf GdejRGf ai Yde GdCOhGQ hGdChRGf HQbe (B46 (3ehSjbis
(3hjdjgG eLehYI ef GdQSGFd efgG aUd ai TQM GdfZeGJ GdePchQI ai GdCQLhRIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B47 s
Keywords: (3GdehSjbi hGdZfGAs